Facile preparation of coal-based ultramicroporous carbon microspheres for selective CO2 capture - Mei An; Tuo Guo; Qingjie Guo (Carbon Resources Conversion, 2024)
The basic structure of aromatic compounds that are abundant in coal is the carbonaceous precursor derived from carbon microspheres. However, it remains to be a huge challenge to prepare carbon microspheres using coal due to the complex construction and composition of coal. Herein, a simple and viable way to obtain coal-based microporous carbon microspheres was developed by means of ethanol pyrolysis and a sequential extraction strategy. The as-prepared carbon microsphere featured aspherical micron particles of a uniform size (0.6–1.6㎛), abundant O-functional groups, excellent thermal stability, high SBET(415.5–983.2 m2/g), and plentiful ultramicropores(63.15–72.72 %). The coal-based carbon microsphere exhibited a noteworthy CO2 uptake (3.19–4.97 mmol/g at 273 K and 1.0 bar), acceptable CO2/N2 selectivity (IAST: 23–46) and moderate isosteric heats (20–32 kJ/mol). This synthetic strategy is important for the preparation of ultramicroporous carbon microspheres using coal, and the synthetic carbon microspheres have promising prospects for highly efficient CO2 capture.